POTENSI BAKTERI ENDOFIT DALAM MENEKAN PENYAKIT LAYU STEWART (PANTOEA STEWARTII SUBSP. STEWARTII) PADA TANAMAN JAGUNG - Rahma, Haliatur; Zainal, Aprizal; Suharman, Memen; Sinaga, Meity S; ., Giyanto (Universitas Lampung, 2014)
Potential of endophytic bacteria to control stewart wilt disease (Pantoea stewartii subsp. stewartii) in maize. The purpose of this study was to explore endophytic bacteria from seedling, maize roots and grass roots as well as to test the ability of endophytic bacteria which could potentially suppress stewart wilt disease development in maize. Characterization of endophytic bacteria as biocontrol agents including: do not induce HR on tobacco, synthesize IAA, dissolve phosphate, produce siderophores, and antibiotic to Pantoea stewartii subsp. stewartii (Pnss). The results of research shoed 17 isolates of endophytic bacteria potentially as candidate biocontrol agents. Nine isolates were able to produce IAA, siderofores and phosphatase; two isolates produce IAA and phosphatase; six isolates produce IAA. Six isolates ie: AR1, AJ34, AJ15, AJ19, and AJ14 AN6, can increase maize plant resistance and suppress stewart wilt disease severity with a range of 48.95-55.60%.